2019
DOI: 10.3390/antiox8120650
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intake of a Grape and Blueberry Polyphenol-Rich Extract Ameliorates Cognitive Performance in Healthy Young Adults During a Sustained Cognitive Effort

Abstract: Despite an increasing level of evidence supporting the individual beneficial effect of polyphenols on cognitive performance, information related to the potential synergistic action of these phytonutrients on cognitive performance during a prolonged cognitive effort is currently lacking. This study investigated the acute and sustained action of a polyphenols-rich extract from grape and blueberry (PEGB), on working memory and attention in healthy students during a prolonged and intensive cognitive effort. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…The cognitive benefits seen here are broadly in line with previous demonstrations of improved cognitive function following both acute [24][25][26] and chronic administration [27,28] of polyphenol rich extracts. Several polyphenol studies also employed the Cognitive Demand Battery used here (but at a single post-dose time point), with demonstrations of improved performance across all three tasks following cocoa-flavanols [24], improved Serial 3s performance following fruit flavanols [50], but no benefits following resveratrol [51]. Of note, the global performance measures derived from the cognitive tasks utilised here have proved sensitive to the acute and chronic administration of a Nepalese pepper extract [42] and acute administration of a green oat extract to middle-aged adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive benefits seen here are broadly in line with previous demonstrations of improved cognitive function following both acute [24][25][26] and chronic administration [27,28] of polyphenol rich extracts. Several polyphenol studies also employed the Cognitive Demand Battery used here (but at a single post-dose time point), with demonstrations of improved performance across all three tasks following cocoa-flavanols [24], improved Serial 3s performance following fruit flavanols [50], but no benefits following resveratrol [51]. Of note, the global performance measures derived from the cognitive tasks utilised here have proved sensitive to the acute and chronic administration of a Nepalese pepper extract [42] and acute administration of a green oat extract to middle-aged adults [41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some more other small colonic metabolites are the object of similar studies, as they have been able to exert anti-inflammatory activity at the neuronal level [73]. In terms of human intervention studies, in a recent trial, an acute supplementation of a grape and blueberry polyphenol-rich extract was found to improve cognitive performance with a major impact on specific cognitive functions, such as working memory and attention [74].…”
Section: Gut-brain Axismentioning
confidence: 99%
“…A growing number of epidemiological studies support a role for polyphenols in the prevention of chronic non-communicable diseases such as cardiovascular disease (CVD) [14], cancer [15] and neurodegenerative diseases [14,16]. Furthermore, animal studies have demonstrated the ability of polyphenols to improve cognitive performance and memory [17,18] and, more recently, these results have been replicated in human studies [19,20]. Regarding mental health, a growing body of data from animal and human studies has emerged supporting the role of a variety of dietary polyphenols in affecting behaviour and mood through anxiolytic and antidepressant-like properties, mediated through multiple molecular and cellular pathways [21].…”
Section: Introductionmentioning
confidence: 99%